Odpowiedzi

2010-02-03T17:33:11+01:00
A)0=3-(2x+1)
0=3-2x-1
0+2x=3-1
2x=2/:2
x=1

b)0=(x-1)-(3x-5)
0=x-1-3x+5
0-x+3x=-1+5
2x=4/:2
x=2

c)3(1-x)-(1-2x)=9
3-3x-1+2x=9
-3x+2x=9-3+1
-x=7/: (-1)
x=-7

d)0,5(2-4x)=3-x
1-2x=3-x
-2x+x=3-1
-x=2/: (-1)
x=-2
2010-02-03T17:35:18+01:00
A)
0=3-(2x+1)
0=3-2x-1
2x=2
x=1

b)
0=(x-1)-(3x-5)
0=x-1-3x+5
2x=4
x=2

c)
3(1-x)-(1-2x)=9
3-3x-1+2x=9
-x=7
x=-7

d)
0,5(2-4x)=3-x
1-2x=3-x
-x=2
x=-2
2010-02-03T17:38:58+01:00
A)0=3-(2x+1)
0=3-2x-1
0+2x=3-1
2x=2/2
x=1

b)0=(x-1)-(3x-5)
0=x-1-3x+5
0=-2x+4
2x=4/2
x=2

c)3(1-x)-(1-2x)=9
3-3x-1+2x=9
2-x=9
-x=9-2
-x=7/*(-1)
x=-7

d)0,5(2-4x)=3-x
1-2x=3-x
-2x+x=3-1
-x=2/*(-1)
x=-2